Man‘s Restoration: Robert of Auxerre and the Writing of History in the Early Thirteenth Century - Neel, Carol (Traditio, 1988)
The historical work of the Premonstratensian canon Robert of Auxerre († 1211) was one of the most influential of medieval chronicles. Vincent of Beauvais († 1264) borrowed heavily from it in Speculum historiale, the final section of his great encyclopedia. The content of the Auxerre chronicle, extant in its independent version in relatively few manuscripts, thus contributed to an essential element in the textual foundation of later medieval education. The shape of Robert's narrative, however, differed from that of Vincent's treatment of history. The canon of Auxerre wrote in an old genre and for a traditional end. His was the kind of monastic chronicle that had for centuries affirmed for Benedictine and reform congregations their connection to venerable tradition, and traced for them the workings of providence in time. Vincent's work, on the other hand, set the record of human experience alongside compendia about the divine and natural worlds. It thus represented the historiographical fulfillment of the thirteenth century's ambition to systematize knowledge.
Keywords: 👤 robert of auxerre

Hermann's Opusculum de conversione sua: truth or fiction? - Saltman, Avrom (Revue des études juives, 1988)
Keywords: 👤 hermann of cologne

The origins of Dundrennan and Soulseat abbeys - Scott, Jack G. (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1988)
Keywords: soulseat